Relationship between vegetation of the levee neo-ecosystems and environmental heterogeneity in the Lower Delta of the Paraná River, Argentina - Kalesnik, Fabio Alberto (2011)
The relationship between environmental heterogeneity and the vegetation of the levee neo-ecosystems in the Delta of the Paraná River was studied. These habitat types were considered plant communities of recent origin related to local productive activities. Vegetation coverage was evaluated in 97 plots of three different environmental units (A, B and C), using classification analysis, indirect and direct ordinations. The differential vegetation in different environmental units could be related to a greater fluvial influence of the Paraná River on unit A and a greater tidal influence of the de la Plata River on units B and C. The Lower Delta hydrological regimes only affect a few of edaphic variables particularly pH, organic matter percentage and clay content. To understand the spatial pattern of neo-ecosystems vegetation, it is also necessary to consider the invasion of alien species that has been taking place for over 50 years.